Impact of low-protein diet on geese growth: early low-protein diets with amino acid supplementation improve nitrogen utilization and maintain growth performance in meat geese - Li, Wenzhong; Zhao, Mengli; Zhang, Lei; Sun, Guobo; Zhao, Hongchang; Zhang, Gansheng; Ji, Rongchao; Wang, Jian; Li, Xiaoming; Chen, Guoshun (Frontiers in Animal Science, 2025)
Herein, 364 one-day-old male Jiangnan white goslings were divided into four groups: PM (18.55% crude protein (CP) + main amino acids (AA)), PA (18.55% CP + all AA), LPM (15.55% CP + main AA), and LPA (15.55% CP + all AA). The main AAs were Lys, Met, Thr, Trp, Arg, and Cys, while all AAs included an additional six (Met, Lys, Arg, His, Ile, Leu, Cys, Phe, Tyr, Thr, Trp, and Val). At 28 days, all geese were switched to a 15.55% CP + main AA diet until 63 days. The results showed: (1) No significant impacts on average daily gain or feed-to-gain ratio at 29-63 days. Although numerical differences in average daily feed intake (ADFI) were observed between groups, statistical analysis indicated that the reduction in ADFI due to early low protein was marginal (P = 0.06). This suggests that the dietary protein level may influence feed intake patterns in goslings, but further studies with larger sample sizes are needed to confirm this effect. (2) Early low protein significantly affected abdominal fat percentage and leg muscle cooking loss at 63 days (P < 0.05). Pretreatment affected breast muscle rate at 63 days (P < 0.05). (3) Early low protein significantly increased Cys content in breast muscle at 63 days and increased Asp, Thr, Cys, and His in feces at 62-64 days (P < 0.05). (4) Early low protein led to a significant reduction in nitrogen excretion and an increase in nitrogen utilization (NU) in feces at 62-64 days (P < 0.05). Low-protein diets reduced nitrogen excretion by 12.3% (1.60 vs. 1.78 g/bird, P < 0.05) and improved nitrogen utilization from 56.03% to 59.48%. Leg muscle cooking loss decreased by 15.2% in the LPA group (15.01%) compared to PA (19.58%, P < 0.05). To conclude, different AA supplementation patterns with low protein (15.55%) in the early stage (1-28 days) had no significant effects on body weight, slaughter performance, and meat quality at 63 days. However, early low protein significantly reduced nitrogen excretion and improved NU, suggesting it is feasible for meat goslings to adopt a low-protein diet supplemented with main AAs during the early stage.